Adopting Industry Based Curriculum Design towards Independent Campus Policy - Gozali Gozali; Ria Setyawati; Bambang Jati Kusuma; Fitriyani Fitriyani (LPPM Universitas Jambi, 2020)
The relevance of the curriculum between vocational education (diploma) and industry needs is still a matter in the world of education in Indonesia. This happens the link and equivalent in the preparation of the education curriculum have not existed. The Indonesian government through the policy of an independent learning and independent campus learns to create appropriate curriculum designs between vocational education and industry. This research is to find out the industrial curriculum design for diploma graduates. The methodology used a study by finding theoretical references that are relevant to the topic and sought through descriptive analysis. the right and appropriate partnership, it can produce curricula based on the industry required by student competencies in four categories, namely (1) Core foundations, (2) Concentrations (3) Experiences (Industry Experience and Internship), (4) Final Projects. These four categories provide an increase in student competencies that are in line with industry needs.